Ensaio clínico randomizado do tratamento com overdenture mandibular retida por um e dois implantes: avaliação de desfechos clínicos, radiográficos, percepção do paciente e análise de custos - Resende, Gabriela Pereira de (2019)
The objective of this study was to perform a randomized clinical trial of two treatment alternatives for the rehabilitation of mandibular edentulism: mandibular overdenture retained by one implant (OVD-1) and mandibular overdenture retained by two implants (OVD-2). A total of 47 edentulous participants were included, allocated to one of the treatment groups. All patients received Standard Plus SLActive® implants (Straumann, Switzerland) installed following the 21-day conventional loading protocol. Primary outcomes involved patient satisfaction with the treatment and impact of oral health on quality of life. Secondary outcomes involve masticatory performance, pain, implant stability (ISQ), marginal bone pattern, peri-implant and aspects of the tissue, clinics and overdenture maintenance events, and the costs that were identified, measured and valued for one year after the treatment. The Wilcoxon, Anova mixed and GEE tests were used to compare the different study groups. The patients underwent a genetic improvement program (p> 0.05), performance masticatory (p = 0.924), related pain (p = 0,491), ISQ (p = 0.128). Bone markers were marginal at 0.31 (± 0.70) and 0.12 (± 0.59) for the OVD-1 and OVD-2 groups, respectively, after 12 months, with no differences between groups (p = 0.370). Regarding peri-implant areas and molar tissue, clinics and overdenture maintenance events were not regretted when compared to statistically significant (p> 0.05). However, it was able to make the difference between the groups in relation to the total time of treatment (p = 0.001), and in relation to the costs that this figure presented in the surgical phase (p = 0.004) and in the prosthetic phase (p <0.001) , representing an incremental cost of R$ 1230.13 for OVD-2 treatment. The results were that the treatments with two implants are equivalent, and the use of a single implant can be a viable alternative for cost reduction and treatment invasiveness.